Pengembangan Bahan Ajar Tematik Berbasis Flipbook Marker untuk Meningkatkan Kemampuan Berfikir Kreatif Anak TK Darul Iman - Wahyuni Wahyuni (Universitas PGRI Semarang, 2022)
AbstractThe background of this research is the low creative thinking ability of children because the teacher has not used the right teaching materials to support learning activities in the classroom. The purpose of this research is to develop flipbook marker-based thematic teaching materials and to find out the effectiveness of using teaching materials to increase children's creative thinking skills in TK Darul Iman. This research was carried out in seven stages using Borg and Gill floating. The seven stages include 7 stages, namely: 1) Potential and Problems, 2) Collecting Data, 3) Product Design, 4) Design Validation, 5) Design Revision, 6) Product Trial, 7) Product Revision. The trial subjects of this study were group A consisting of 17 students at TK Darul Iman. The learning process is carried out with a one group pretest and posttest design. Data collection techniques were sourced from questionnaires from material validation experts, media validation experts, observations, interviews, and documentation. The results of this study indicate that (1) the validity test of material experts is 92 with a very valid category, the validity test of media experts is 92.14 with a very valid category. (2) the average response of children is 93.01%, (3) the average teacher response is 92.78% with a very practical category. (4) the value of the Paired Samples T Test obtained a significance value of 0.000 <0.05, then the hypothesis is accepted. This shows that flipbook marker-based thematic teaching materials are effective for improving children's creative thinking skills.Keywords: thematic teaching materials, flipbook markers, creative thinking AbstrakLatar belakang penelitian ini rendahnya kemampuan berfikir kreatif anak dikarenakan guru belum menggunakan bahan ajar yang tepat untuk menunjang kegiatan pembelajaran di kelas. Adapun tujuan dari penelitian ini yaitu untuk mengembangkan bahan ajar tematik berbasis flipbook marker dan mengetahui efektifitas pengguanaan bahan ajar terhadap peningkatan kemampuan berfikir kreatif anak di TK Darul Iman. Penelitian ini dilaksanakan dalam tujuh tahapan menggunakan pengambangan Borg and Gill. Tujuh tahapan meliputi meliputi 7 tahap yaitu: 1) Potensi dan Masalah, 2) Mengumpulkan Data, 3) Desain Produk, 4) Validasi Desain, 5) Revisi Desain, 6) Uji Coba Produk, 7) Revisi Produk. Subyek uji coba penelitian ini adalah kelompok A yang terdiri dari 17 siswa di TK Darul Iman. Proses pembelajaran dilaksanakan dengan desain one group pretest dan posttest design. Teknik pengumpulan data bersumber dari angket ahli validasi materi, ahli validasi media, observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa (1) uji validitas ahli materi 92 dengan kategori sangat valid, uji validitas ahli media 92.14 dengan kategori sangat valid. (2) rata-rata respon anak 93.01%, (3) rata-rata respon guru 92,78% dengan kategori sangat praktis. (4) nilai uji Paired Samples T Test diperoleh nilai signifikansi 0.000 < 0.05 maka hipotesis diterima. Hal ini menunjukkan bahan ajar tematik berbasis flipbook marker efektif untuk meningkatkan kemampuan berfikir kreatif anak.Kata kunci: bahan ajar tematik, flipbook marker, berfikir kreatif